TRANSLATING AND ANALYZING TRANSLATION METHODS, APPROACHES, AND TECHNIQUES IN STORIES “AL-ASADU WAL FA’RU” - Padilillah, Rahma; Janah, Nuryatul; Awalludin, Muhammad (Jurnal Al-Hibru, 2025)
This journal discusses the process of translating a classic Arabic fable story entitled Al-Asadu Wal Fa’ru (The Lion and the Mouse) into Indonesian. This story is a type of narrative fiction that contains moral values with animal characters that represent human nature and behavior. This study aims to identify and analyze the methods, approaches, processes, and techniques used in translating the text. The focus of the analysis is directed at the entire content of the story to understand how moral messages and narrative structures in the source language can be effectively transferred into the target language without losing meaning and cultural nuances. The results of the study show that the translation method applied in this text is a communicative method, which attempts to convey messages clearly and easily understood by the target reader. The most dominant technique used is the common equivalence technique, which prioritizes the use of equivalent words or expressions that are often used in Indonesian. In terms of ideological approach, this translation tends to use a domestication approach, namely adjusting elements of foreign culture so that they feel familiar and acceptable to local readers. Thus, it is hoped that this research can provide a useful contribution in the application of translation theories, especially in translating classical Arabic literary narrative texts, as well as increasing understanding in developing translator competence in the fields of Arabic literature and language.